Alexander Lee, Humanism and Empire, The Imperial Ideal in Fourteenth-Century Italy. Oxford University Press: Oxford 2018. - Steiris, Georgios (Conatus - Journal of Philosophy, 2019)
Book review of Alexander Lee, Humanism and Empire, The Imperial Ideal in Fourteenth-Century Italy (Oxford University Press: Oxford 2018). By Georgios Steiris, National and Kapodistrian University of Athens, Greece